MULTILINGUAL PRACTICES IN THE EFL CLASSROOM: INVESTIGATING CODE-SWITCHING TYPES, FUNCTIONS, AND STUDENTS' PERCEPTIONS - Rahmat Solihin; Novitri; Supriusman (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2025)
Code-switching, the practice of alternating between two or more languages within discourse, constitutes a significant pedagogical strategy in English as a Foreign Language (EFL) instruction. This study examines the types and pedagogical functions of code-switching employed by English teachers across five junior high schools in Pekanbaru, Indonesia. Utilizing a mixed-methods research design involving classroom observations, semi-structured teacher interviews, and student questionnaires, the study identifies three types of code-switching: intra-sentential, inter-sentential, and tag switching. The findings reveal that intra-sentential code-switching was the most frequently employed form. Teachers primarily used code-switching to elucidate difficult concepts, maintain classroom management, and foster interpersonal connections with students. Most students responded favorably, indicating that code-switching enhanced their comprehension and created a more supportive classroom environment. Nevertheless, some students expressed concern that excessive reliance on the first language might hinder their English proficiency. The study concludes that code-switching, when used judiciously, can serve as an effective pedagogical tool that facilitates both cognitive and linguistic development in EFL classrooms.